Psychic Distance That the Public Aspired to: Emotional-Social Processes Reflected in the Audiovisual Resources in Triunfos de Amor y Fortuna - Rozenbergaite, Ieva Emilija (Talía. Revista de estudios teatrales, 2023)
Antonio de Solís y Ribadeneyra’s Triunfos de amor y fortuna represents one of the major delights of the 17th century Spanish Theatre, while its succession of performances during the epoch reached more than sixty. This circumstance makes us reflect on the nature of the connection between the audience and the play and also about the Golden-age viewer’s expectations perfectly fulfilled by the comedia. Therefore, the present article analyzes the sensory, emotional and intellectual stimulations transmitted by the staging of Triunfos de amor y fortuna from an aesthetic perspective, or, more precisely, by applying the concept of psychic distance. Considering the huge importance of the highly spectacular visual effects and numerous musical interventions, the study focuses on the audio-visual resources of the play.